Exceptional oxygen consumption, values and relationships: An analysis from Exercise Physiology - Cofré‐Bolados, Cristian; Vidal Diaz, Félix; Herrera-Valenzuela, Tomás; Farias-Valenzuela, Claudio; Espinoza-Salinas, Alexis; Galeano-Rojas, Dilan (SPORT TK-EuroAmerican Journal of Sport Sciences, 2024)
Maximum oxygen consumption VO2max has represented a fundamental reference when measuring cardiorespiratory fitness in different sports. The aim of this study was to present the results of ergometry tests with gas analysis in athletes who exceeded 70 ml/kg/min in VO2max, analyzing the correlations between VO2max and metabolic, cardiovascular, and respiratory parameters. The study was of a descriptive correlational type, and 27 male athletes participated. The r Pearson test was applied to determine the correlation between the variables. In the result analysis, correlations were determined: small between Age and VO2max (r = -0.238; p = 0.24); large between VO2max vs VO2VT1 (r = 0.741; p<0.001); VO2max vs VO2VT2 (r = 0.808; p<0.001); and VO2VT1 vs VO2VT2 (r = 0.783; p<0.001). Mean between VO2max and HR (r = 0.340; p = 0.09); large between absolute VO2max and VO2/HRmax (r = 0.840; p<0.001); small between VO2max and VE (r = 0.214; p = 0.30); small between VO2max and BR (-0.184; p = 0.37); small between VE and RR% (r = -0.281; p = 0.164). There were large correlations between VO2max and ventilatory thresholds, and there was also a large correlation between absolute VO2max and oxygen pulse, with small and non-existent correlations between VO2max and ventilatory parameters.